Safety and health risk assessment of a traditional Indonesian market - Gusti, Aria; Fitriyani, Fitriyani (Public Health of Indonesia, 2022)
Background: The activities of traders and visitors in the market have potential hazards that pose safety and health risks. Thus, understanding the risks and the threats is a necessity. Objective: This study aimed to identify hazards, analyze safety and health risks, and design risk control efforts that market managers can apply. Methods: This research was qualitative research with an observational approach. The informants were selected purposively: the head of the Siteba Market Technical Implementation Unit, security officers, traders, and visitors at the Siteba Market, Padang City, Indonesia. The instruments used were checklists and interview guides. Risks were analyzed manually based on the AS/NZS 4360 standard matrix. Results: The research results using the elicitation method identified ten potential safety and health hazards in Siteba Market. The safety and health risks for traders and visitors to Siteba Market consisted of seven high risks and three medium risks. Potential high risks were accidents, pickpockets, fatigue, slipping, falling, and jostling during emergencies and fires. Meanwhile, the potential risks consisted of traffic jams, indigestion, and scattered merchandise. Conclusion: Traders and visitors were potentially exposed to safety and health. Community organizing efforts through the occupational health business post need to be activated by the health centers to carry out preventive and promotive measures for safety and health in the market.